Consumer Psychology of Tourism, Hospitality and Leisure. Volume 2 2001
DOI: 10.1079/9780851995359.0049
|View full text |Cite
|
Sign up to set email alerts
|

The impact of seemingly minor methodological changes on estimates of travel and correcting bias.

Abstract: In 1998, evidence was provided suggesting that an apparent 15% decline in domestic travel estimated from the Canadian Travel Surveys (CTS) of 1994, 1996, and 1997 was possibly misleading. This decline could actually be the result of methodological changes in the survey rather than a change in travel behaviour. Here, realistic assumptions and a simple computational method are utilized to demonstrate that change in bias may account for the drop in estimated trips. The analysis depends on a trip recall salience s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Bias can also occur when respondents approximate answers by rounding estimates to numbers ending in zero or 5 (Hultsman et al 1989, Vaske et al 1996, Beaman et al 1997. In a situation where participation or harvest was actually 23, the response may be 20 or 25.…”
Section: Cognitive Processes In Harvest Survey Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bias can also occur when respondents approximate answers by rounding estimates to numbers ending in zero or 5 (Hultsman et al 1989, Vaske et al 1996, Beaman et al 1997. In a situation where participation or harvest was actually 23, the response may be 20 or 25.…”
Section: Cognitive Processes In Harvest Survey Responsesmentioning
confidence: 99%
“…For example, if days of participation was 7, the multiplier use neighborhood was potentially ±3 around a multiple of 7. As 0-5 heaps have an unknown but potentially large influence on the distribution of responses in multiplier neighborhoods (Vaske et al 1996, Beaman et al 1997, Vaske et al 2003, 0-5 responses were not included in multiplier neighborhoods. In the days = 7 example, if there is no preference for a multiplier of 2, about 1/7 of the responses for the neighborhood would fall on 14 if it were not for 0-5 heaping on 15.…”
Section: Measuring Response Heapingmentioning
confidence: 99%
See 1 more Smart Citation
“…Chu, Eisenhower, Hay, Morgenstein, Neter, and Waksburg (1992) suggest the bias is quite large. Using PSHC could possibly reduce bias in total harvest for Illinois from 50% to 35%, from 30% to 15%, from 7% to 5%, or (Beaman et al, 2000), the need for a 15% bias correction was identified with changes in survey methodology considered unimportant at the time of the survey. Benchmarks that could be estimated were certain types of international trips by Canadians (Auctor, 1998).…”
Section: Downloaded By [New York University] At 02:01 15 June 2015 Comentioning
confidence: 99%
“…The abrupt change in methodology means the use of the old data may be minimal. This is because one generally does not know what part of change in estimates between old and new ones is a result of change in bias and what part is a result of change in behavior (Beaman, Beaman, O'Leary, & Smith, 2000;Kunert, 1998). Is there a conundrum?…”
mentioning
confidence: 97%